2000
DOI: 10.1053/jhep.2000.20456
|View full text |Cite
|
Sign up to set email alerts
|

Results of Surgical and Nonsurgical Treatment for Small–Sized Hepatocellular Carcinomas: A Retrospective and Nationwide Survey in Japan

Abstract: Hepatic resection (HX), percutaneous ethanol injection (PEI), and transcatheter arterial embolization (TCAE) have all been used in the treatment of patients with small-sized hepatocellular carcinomas (HCCs). However, the indications for these therapeutic modalities remain unclear. Therefore, the first step to minimize the debate on these indications is to review the standard results from each treatment based on an extensive survey. The participants in this study were patients with HCCs less than 5 cm in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
468
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 693 publications
(493 citation statements)
references
References 19 publications
16
468
1
8
Order By: Relevance
“…No RCTs have demonstrated that surgical resection is superior to percutaneous ablation. In nonrandomized comparative studies, hepatectomy was better than percutaneous ablation in one study [213] whereas others reported no significant difference between the two therapies [310][311][312]. Thus, it is difficult to conclude that surgical resection is the treatment of choice for resectable HCC.…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
See 1 more Smart Citation
“…No RCTs have demonstrated that surgical resection is superior to percutaneous ablation. In nonrandomized comparative studies, hepatectomy was better than percutaneous ablation in one study [213] whereas others reported no significant difference between the two therapies [310][311][312]. Thus, it is difficult to conclude that surgical resection is the treatment of choice for resectable HCC.…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
“…Furthermore, small, arterially enhancing nodules are common in the cirrhotic liver, and majority of these nodules are benign [209][210][211]. Therefore, the most important issue remains the identification of small tumors because curative treatments can be optimally applied to improve outcome [212,213]. If left alone, these tumors can grow aggressively and invasion can occur before tumors reach the 2-cm cutoff size for small HCC [202].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
“…Many studies have reported that HCV infection is an independent factor for MO HCC and that the MO occurrence rate is higher in the presence of HCV than HBV (Arii et al, 2000;Poon et al, 2000). Maeda et al (2000) reported a higher rate of new poorly differentiated neoplasms when HBV-associated HCC recurred.…”
Section: Discussionmentioning
confidence: 99%
“…RFA particularly have emerged as a promising adjunct in the treatment of CLM and HCC in the past decade due to its safety, efficacy, and ability to provide more consistent results in local tumor control, especially in patients with limited hepatic reserve. 10,11 While there have been several studies evaluating 5-year survival in small cohorts of patients undergoing RFA as part of their treatment strategy for HCC or CLM, there are only limited data on 10-year survival, which is a time interval that we believe is equivocal with cure. 3,[12][13][14][15] In this study, we sought to determine whether long-term overall survival at 10 years is obtainable in patients, who undergo RFA as part of their treatment for primary and metastatic colorectal hepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%